Reflections on waterfronts within the context of urban intervention (Huellas, 2016)
This paper reflects on the problem of waterfronts in relation to the processes of urban revitalization. The methodology applied aims at looking for general and specific literature in order to compare different perspectives of study, taking into account the following: the changes that have taken place as well as the impacts on space dynamics; the social and economic problems observed and the forms of articulation mainly between urban policies and agents participating on these spaces. Generally speaking, at the moment of their study, waterfronts present complexities due to strong differences in their natural conditions and, also, because of the actions proposed to be carried out on them. Large interventions, in general, have copied an intervention model, whose features are exclusive use associated to the creation of new spaces of consumption. Urban policy assumes a role of utmost importance given that it should be flexible but at the same time it should establish regulations and instruments that allow market regulation, ensuring that interventions are not only based on the cost-benefit relation, economically speaking, but also on the social condition of public spaces as inseparable part of the urban experience.
Keywords: waterfronts; urban space; interventions; urban dynamics.